Islamic Values in Mathematics Education: A Bibliometric Analysis with Emphasis on Educational Management Trends - Hamdanah, Hamdanah; Crismono, Prima Cristi; Yakoh, Mahnawawe (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the integration of Islamic values in mathematics education through a bibliometric approach, with a focus on trends in educational management. The background of this research lies in the growing attention to value education within the context of holistic education, alongside the lack of systematic mapping regarding the relationship among the concepts of